Plan de marketing del observatorio de Comercio exterior e inversión extranjera-Universidad de Otavalo - Granja, Diana B. (2019)
his research proposes a marketing plan for the Observatory of Foreign Trade and Foreign Investment of the University of Otavalo where a theoretical scheme is proposed that allowed to support the purpose of this academic project so that society knows the functions that this academic center performs and the benefits that it will bring to the area of foreign trade. This document in its global content is structured with an introduction and three chapters such as: theoretical framework, methodological development, research results, as well as conclusions and recommendations.